2005
DOI: 10.1117/12.630877
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz imaging system performance model for concealed weapon identification

Abstract: The U.S. Army Night Vision and Electronic Sensors Directorate (NVESD) and the U.S. Army Research Laboratory have developed a terahertz (THz) -band imaging system performance model for detection and identification of concealed weaponry. The MATLAB-based model accounts for the effects of all critical sensor and display components and for the effects of atmospheric attenuation, concealment material attenuation, and active illumination. The model is based on recent U.S. Army NVESD sensor performance modeling techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It has been shown that commonly used explosives have a number of spectral features in the THz region, which can be used to identify the explosive, [8,13,14,16,32,34,35] even if concealed behind optically opaque materials. [10,36,37] It has also been shown that a range of plasticisers and dyes used in the manufacture of explosives are transparent in the terahertz region and thus identification of the explosive in these complex mixtures remains possible. [16] Although spectral features of a large range of explosives have been identified, it is only recently that the origin of these modes has been ascribed and predicted accurately, using theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that commonly used explosives have a number of spectral features in the THz region, which can be used to identify the explosive, [8,13,14,16,32,34,35] even if concealed behind optically opaque materials. [10,36,37] It has also been shown that a range of plasticisers and dyes used in the manufacture of explosives are transparent in the terahertz region and thus identification of the explosive in these complex mixtures remains possible. [16] Although spectral features of a large range of explosives have been identified, it is only recently that the origin of these modes has been ascribed and predicted accurately, using theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…This comparison of ZBD versus pyroelectric detector response was used to fit to a second order polynomial and then used to linearize the measured ZBD power. The scattered power levels on the ZBD were typically more than 40 dB lower than the source power, well into the ZBD linear regime, but the linearization was necessary to properly establish the incident power on the target, P i of Equation 1. Compression (saturation) in the ZBD response led to about a 2 dB correction in P i .…”
Section: Instrument Designmentioning
confidence: 98%
“…The bidirectional scattering distribution function (BSDF) and the area normalized bidirectional radar cross section (σº) are related concepts and are needed to determine detection threshold levels in radars and other active imagers [1,9]. Since our measurement geometry is reflective, BSDF is equivalent to bidirectional reflectance distribution function (BRDF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murrill et al, has adapted the latest U.S. Army NVESD sensor model to accommodate THz imaging 3 . A defined target set consisting of small handheld weapons was blurred in a known fashion and then used in a perception experiment to determine task difficulty (V 50 ) for the soldier.…”
Section: Introductionmentioning
confidence: 99%